Role of Profitability, Business Risk, and Intellectual Capital in Increasing Firm Value - Dewi Pangestuti; Ali Muktiyanto; Ira Geraldina; Darmawan Darmawan (Journal of Indonesian Economy and Business, 2022)
Introduction/Main Objectives: This research illustrates the importance of firm value, both to investors and companies. Investors assess that an increase in the value of a company indicates a positive view of the company's performance, which leads to an investment decision. Besides that, an increase in the value of the company can indicate that the company is getting closer to achieving its goal, namely increasing the welfare of its stakeholders. Background Issues: In recent years, there has been a decline in the value of firms in the mining sector due to various factors that have affected it, which has resulted in a decrease in the value of the shares in several of the sub-sectors, especially the coal mining and petroleum sub-sectors. Novelty: This study examines the business risk and intellectual capital that are typical of firms in the mining industry with the generalized moments’ methods. Research Methods: This research is a quantitative study that uses the generalized moments methods, where the robust least square test determines which model is more suitable for use in the research. The variables in this study consist of profitability, intellectual capital, and business risk, with variable controls being the gold price, exchange rate, and petroleum price. This study uses annual financial statements from mining companies that are listed on the Indonesia Stock Exchange. These statements include balance sheets and income statements. Finding/Results: These findings reveal that profitability, intellectual capital, and business risk affect the value of a company. Macroeconomic factors as the variable controls, namely gold prices, exchange rates, and petroleum prices, also affect the value of a company. Therefore, based on the research’s results, management must pay attention to internal factors or company micro factors (profitability, intellectual capital, and business risks) and macroeconomic factors (gold prices, exchange rates, and petroleum prices) to increase company value. This is because investors use these factors when making decisions to invest in the mining sector. Conclusion: There are several important factors that, in principle, increase the value of a company. These factors come from internal and external factors (macroeconomics). This article successfully demonstrates the importance of profitability, intellectual capital, and business risk in supporting firm value. The results also showed that the gold price, exchange rate, and the price of oil have an effect on the price of mining stocks, which are used to measure changes in the economy